ISSUES AND CHALLENGES OF SHARIAH AUDITING IN ISLAMIC FINANCIAL INSTITUTION AND CORPORATE GOVERNANCE COMPLIANCE - Agus Arwani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The study examines the perspective of practitioners who are involved directly and/or indirectly with the process of shariah compliance/auditing from Islamic financial institutions (IFIs) on the issues of standards for shariah auditing, auditors qualifications, and independence. Auditing Islamic financial institutions (IFIs) covers a wider scope than legal financial statement auditing. External auditors of IFIs not only conduct financial audits but also conduct tests on the shariah compliance of IFIs, according to fatawa (religious opinions) and guidelines set by the Shariah Supervisory Board (SSB). Shariah review is unique to IFIs, due to the requirement to ensure that all business activities and operations of IFIs adhere to shariah precepts. The scarce resourceful auditors with both shariah and accounting/auditing qualifications and the issue of self-review threat to independence may affect the reputable image of Islamic financial institutions. This article is literature method. The findings reinforce the importance of auditors' qualification and independence as currently there is no mandatory regulated professional shariah auditor code to be in tandem with the drastic growth of the IFIs. The paper offers practical implication to regulators in providing a direction to revise the existing standards for shariah auditing practices and to formulate a mandatory professional governance structure for shariah auditors.